Organic Vegetables Business Development Strategy: A Case Study on Deedad Hydroponic Makassar - Dini Dwiyanti Anwar; Marhawati; Nurdiana; Inanna (Open Global Scientific Journal, 2023)
Vegetable crops have bright prospects for development because they are a complement to staple foods and have high economic value. However, there are many challenges in establishing and running a hydroponic vegetable business so that the appropriate strategy is needed. This study aims to determine the internal and external factors that influence the development of organic vegetable business and to study the development strategy of organic vegetable farming business at “Deedad Hydroponic” Makassar. The type of research conducted was descriptive research using a qualitative approach. The type of informants were determined purposively, namely people who run organic vegetable businesses at “Deedad Hydroponic”. The data collection procedures included observation, interview, and documentation. The data obtained were then analyzed qualitatively using SWOT analysis. The results of the analysis have suggested that the S-O strategies that can be applied are maintaining the freshness and cleanliness of the vegetables, providing training to employees to improve skills and providing equipment in accordance with the latest technology, and expanding marketing networks. W-O strategies that can be applied are conducting continuous promotions to gain market and customer loyalty, and attracting public interest in organic products. S-T strategies that can be applied are innovating high-value product development to face competition, and developing technology-oriented businesses. W-T strategies that can be applied are building a joint product distribution system, and building a network of cooperation to create reliable business governance and technology.